The Growth and Impact of e-Filing in Indonesia - Nurul Izzah Lubis; Tengku Eka Susilawaty; Benny Lyanto (ACCUMULATED JOURNAL, 2022)
e-Filing is an application provided by the Directorate General of Taxes to facilitate taxpayers in reporting their Annual SPT and as a support to increase state revenue from tax sector. This study aims to find out how the growth and impact of e-Filing in Indonesia over a period of 7 years, namely 2014 to 2020 and what things the government should do in order to maintain or increase the use of e-Filing as a means of receiving tax in Indonesia. This type of descriptive research is carried out with a desk study approach where both types of qualitative and quantitative data are used and taken from trusted secondary data sources. The conclusion of this research is the average percentage of e-Filing users compared to the number of registered taxpayers who are required to SPT for a period of 7 years is only 39% and that the growth of e-Filing users is indicated to decline from 2017 to 2020. In order to maintain or increase the use of e-Filing in Indonesia, government must continue to improve the quality of e-Filing in terms of ease of access, trust, environmental interaction functions, reliability, display of information content, support for users, and responsiveness to feedback, continuing socialization and counseling activities, accelerate the mandatory use of e-Filing in reporting SPT and focus on the growth of compliance ratio of each taxpayers division.